Application of Clinical Scores in the Differential Diagnosis of Chronic Rhinosinusitis With Nasal Polyps in a Chinese Population. Issue 3 (May 2020) - Xu, Qingqing; Du, Kun; Zheng, Ming; Duan, Su; Jia, Shuangshuang; Chen, Hui; Wang, Xiangdong; Zhang, Luo
Background: Eosinophilic (Eos) and non-eosinophilic (non-Eos) chronic rhinosinusitis with nasal polyps (CRSwNP) react differently to clinical treatment, with eosinophilic chronic rhinosinusitis with nasal polyps (Eos CRSwNP) being more likely to recur after surgery. Objective: To explore the clinical value of the visual analog scale (VAS), nasal endoscopy score (Lund–Kennedy, L–K), computed tomography (CT) score (Lund–Mackay scoring system, L–M), and blood Eos percentage in the differential diagnosis of Eos CRSwNP and non-Eos CRSwNP. Methods: Ninety-nine patients with CRSwNP were enrolled in this study and assigned to 2 groups (Eos CRSwNP and non-Eos CRSwNP). The blood Eos percentage and VAS, L–K, and L–M scores in the 2 groups of patients were compared. A receiver operating characteristic (ROC) was used to assess the usefulness of VAS, L–K, and L–M scores for differentiating Eos CRSwNP and non-Eos CRSwNP. Results: There were significantly differences between the Eos CRSwNP group and non-Eos CRSwNP group in the following scores: blood Eos percentage, mean VAS score, olfaction/VAS, general discomfort/L–K, edema score/L–K, olfactory cleft (OC) score via endoscopy, mean L–M score, anteriorethmoid sinus score, posterior ethmoid sinus score, sphenoid sinus score, frontal sinus score, and OC score via CT. An ROC analysis showed that blood Eos percentage had the highest area under the ROC curve (AUC) value (0.749); however, several other scores (olfaction score/VAS, edema score/L–K, and mean L–M score) also had high AUC values. The combination of olfaction score/VAS and blood Eos percentage had the highest clinical convenience score as well as high sensitivity and specificity. A combination of cutoff values for the 2 predictors (blood Eos percentage ≥3.85%, olfaction score/VAS score ≥3) showed a sensitivity of 75.5% and a specificity of 78.0%. Conclusion: The olfaction score/VAS score and the blood Eos percentage can be combined to differentiate Eos CRSwNP from non-Eos CRSwNP in a Chinese population.